The Meaning of Persons with Disabilities in Communities in Da’wah Rules in the City of Parepare - Nurkidam, A.; Asmar, Afidatul; Haq, Ahmad Dhiyaul (KARSA Journal of Social and Islamic Culture, 2022)
Sometimes, People with disabilities are underestimated by some people. Even though the government has made a law that contains the rights of persons with disabilities, as contained in Law Number 8 of 2016 about Persons with Disabilities. Islam is a religion of rahmatan lil’alamin, which has its meaning for persons with disabilities. It is implied from the sources of Islamic teachings in the form of the Qur’an and Hadith. Therefore, the existence of government regulations and religious teachings contained in the two sources of Islamic teachings regarding persons with disabilities can influence the attitude of the people in Parepare City to interact with disabilities. This research is field research with a qualitative approach. Data were obtained from interviews, observations, and documentation. Research informan consisted of students, the general public, persons with disabilities, employees of the Social Service Office of Parepare City, and employees of the Ministry of Religion of Parepare City. The study found that most people of Parepare city defined persons with disabilities as not physically limited. In addition, the community can practice ‘da’wah’ towards people with disabilities with quotes (lectures) and their responses and attitudes towards people with disabilities. As a result, the community can behave and walk according to Islamic religious guidance toward persons with disabilities. In addition, the community can also develop related policies for persons with disabilities.